The Novel Numerical Solutions of Conformable Fractional Navier-Stokes Equation with the Robust Method - Alkan, Aslı; Bulut, Hasan; Akturk, Tolga (My University, 2025)
In this study, new numerical solutions of the conformable fractional Navier-Stokes equation are obtained by the conformable q-Shehu homotopy analysis transform method. The fractional Navier-Stokes equation is an extension of the classical Navier-Stokes equations that incorporates fractional derivatives to account for complex flow behaviors such as memory effects and anomalous diffusion. It is particularly useful in describing fluid dynamics in non-Newtonian fluids, porous media, and other systems with intricate time or spatial dependencies. In addition, two and three-dimensional graphs of the obtained solutions were drawn. We also conduct an error analysis to evaluate the accuracy of the scheme. Computational simulations are performed to validate the accuracy of the upcoming method. This paper presents the conclusions derived from the numerical and graphical analysis.
Keywords: Shehu transform; Navier-Stokes equation; Conformable q-Shehu homotopy analysis transform method